Management of esophageal perforations in infants by endoscopic vacuum therapy: a single center case series - Dominik J. Kaczmarek; Dominik J. Heling; Christian P. Strassburg; David Katzer; Gesche Düker; Joanna Strohm; Andreas Müller; Andreas Heydweiller; Tobias J. Weismüller (BMC Gastroenterology, 2022)
Abstract Background Endoscopic vacuum therapy (EVT) has become a standard treatment method for esophageal perforations in adults. However, experience with EVT in infants is scarce. In this retrospective case series, we report on four very young infants who were successfully treated with EVT for esophageal perforations of different etiology. Methods Four infants were diagnosed with esophageal perforations on day 7, 32, 35 and 159 of life, respectively. The youngest one was prematurely born in the 31st week of pregnancy weighing 980 g only. Three infants had perforations due to foreign body insertion (nasogastric tube or pulling through of percutaneous endoscopic gastrostomy (PEG) tube through the esophagus). One child had an anastomotic dehiscence after Foker’s surgery for atresia. In three children EVT was applied as first-line therapy for perforation, in one child EVT was a rescue therapy due to persisting leakage after surgical closure involving thoracotomy. Depending on the esophageal diameter, either an open-pore drainage film or polyurethane sponge was attached to a single-lumen 8 Fr suction catheter, endoscopically (or fluoroscopically by wire-guidance) placed into the esophagus (intraluminal EVT) and supplied with continuous negative pressure (ranging between 75 and 150 mmHg). The EVT system was exchanged twice per week. Results Complete closure of the perforation/leakage could be achieved in all four infants (100%) after 22 days of continuous EVT (median value; range 7–39) and 4.5 EVT exchanges (median value; range 1–12). No serious adverse events occurred. Conclusions EVT is an effective and safe addition to our therapeutic armamentarium in the management of esophageal perforations irrespective of its etiology. Here we prove the feasibility of EVT even in very young infants. The use of an extra thin vacuum open-pore drainage film is helpful to cope with the small esophageal diameter. EVT settings and exchange rates similar to those known from adult treatment were used.